A Toolbox for Lithium–Sulfur Battery Research: Methods and Protocols. Issue 7 (12th June 2017) - Zhang, Ge; Zhang, Ze‐Wen; Peng, Hong‐Jie; Huang, Jia‐Qi; Zhang, Qiang
Abstract : Favorable characteristics, such as high energy density, cost efficiency, and environmental benignity, render lithium–sulfur (Li–S) batteries a promising candidate to meet the increasing demand for efficient and economic energy‐storage systems. Many efforts have been devoted to and much progress has been achieved in Li–S‐battery research from both the scientific and technological viewpoints. Various tools, methods, and protocols have been developed for Li–S‐battery research. Here, these advancements are summarized, from spectroscopic to electrochemical techniques, and the landscape of Li–S chemistry is painted from reactions to transport phenomena. The aim is to provide a comprehensive toolbox for Li–S‐battery research and spur future development in multi‐electron chemistry, multiphase conversion, and related energy‐storage systems and fields. Abstract : Lithium–sulfur (Li–S) batteries represent a promising candidate for efficient and economic energy‐storage systems. The advancements in tools, methods, and protocols are summarized, and the landscape of Li–S chemistry painted, reflecting a comprehensive toolbox for Li–S battery research.